ESTIMATIVA DAS EMISSÕES DE NUTRIENTES (N e P) NA BACIA HIDROGRÁFICA DO RIO JACARAÍPE – SERRA (ES) E POTENCIAL DE EUTROFIZAÇÃO ESTUARINA - Bignotto, Nathalia Ribeiro (2020)
Estuarine systems experience several pressures from coastal zone accelerated and unplanned occupation. Thereby, coastal lagoons show great vulnerability to environmental impacts, mainly, artificial eutrophication, which results in the loss of ecological i